Understanding the effect of sputtering pressures on the thermoelectric properties of GeTe films - Daichakomphu, Noppanut; Abbas, Suman; Chou, Ta Lei; Chen, Li Chyong; Chen, Kuei Hsien; Sakulkalavek, Aparporn; Sakdanuphab, Rachsak (My University, 2022)
In this work, we study the effect of sputtering pressures on the thermoelectric properties of GeTe films. The working pressures were differentiated from 3 to 30 mTorr, and the as-deposited films were annealed at 623 K for 10 min in Ar atmosphere. The results show that the working pressure has a significant effect on the Ge content and crystalline size. The turning trend of the Seebeck coefficient with different sputtering pressures corresponds to the Ge content. The surface morphology of annealed film will change from cracks to voids with increasing sputtering pressure. This behavior can be explained by the growth mechanisms model. The voids and relatively low crystalline size of GeTe films affect to the reduction of the electrical conductivity. In addition, the void content decreased as film thickness was increased. Therefore, controlling the working pressures in the sputtering process and film thickness is important for the thermoelectric performance of GeTe thin film. In our work, we prove that the thermoelectric properties of GeTe films could be optimized effectively by simply tuning different sputtering conditions.
Keywords: GeTe film; RF magnetron sputtering; Thermoelectric; Working pressure